Postpartum Hemorrhage - Michelle J. Wang; Yinka Oyelese; Yang Pan (Maternal-Fetal Medicine)
Abstract. Obstetric hemorrhage is the leading cause of maternal death in childbirth; it is estimated that one woman dies every four minutes from postpartum hemorrhage (PPH). PPH is the cause of approximately one-quarter of maternal deaths worldwide and is thus a major public health issue of great importance. Despite modern advances in medicine, hemorrhage continues to lead the causes of pregnancy-related death in most countries, with increasing disparity between countries with highly developed and underdeveloped national healthcare systems. Most deaths caused by PPH are preventable. All involved in the care of pregnant women must be aware of the gravity of this problem, ways of identifying women at risk for severe hemorrhage at childbirth, strategies for preventing and ameliorating blood loss at delivery, and finally ways to deal with obstetric hemorrhage when it does occur. This article reviews the impact of obstetric hemorrhage, the controversy regarding definitions, diagnosis, epidemiology, pathophysiology, and management of obstetric hemorrhage.